Body mass index, exercise capacity and functional status in chronic heart failure - Steve R. Noumegni; Arnaud D. Kaze; Gregg C. Fonarow; Justin B. Echouffo-Tcheugui (BMC Cardiovascular Disorders)
Abstract Aims This short communication aims to assess the associations of body mass index (BMI) with key functional parameters, including exercise tolerance and functional status, among individuals with chronic heart failure. Methods and results From four chronic heart failure studies ( HF-ACTION [Heart Failure: A Controlled Trial Investigating Outcomes of Exercise Training], NEAT-HFpEF [Nitrate’s Effect on Activity Tolerance in Heart Failure With Preserved Ejection Fraction (HFpEF)], INDIE-HFpEF [Inorganic Nitrite Delivery to Improve Exercise Capacity in HFpEF], and RELAX-HFpEF [Phosphodiesterase-5 Inhibition to Improve Clinical Status and Exercise Capacity in Heart Failure with Preserved Ejection Fraction]), we studied 2,546 participants (mean age: 60.2 ± 12.8 years, 67.8% men, 43.7% non-Whites individuals, 83% with heart failure with reduced ejection fraction (HFrEF), 17% with heart failure with preserved ejection fraction [HFpEF]). Among them, 52.8% had obesity [n = 1344], 29.8% were overweight [n = 758], and 17.4% had a normal body mass index [n = 444]). One-unit increment in BMI (kg/m2) was associated with a lower 6MWT-D (β: -2.78, 95% CI: -3.54, -2.02), a lower VO2max (β: -0.18, 95% CI: -0.21, -0.15), a lower VO2AT (β: -0.10, 95% CI: -0.12, -0.08), a lower RERpeak (β: -0.003, 95% CI: -0.004, -0.002), a lower QoL (β for ln [KCCQ score]: -0.005, 95% CI: -0.008, -0.002), but not with HRpeak (β: β: -0.04, 95% CI: -0.20, 0.11). After adjustment for confounders, individuals with obesity (BMI ≥ 30 kg/m2) compared to those with a normal BMI had lower 6MWT-D (beta coefficient [β]: -21.02, 95% CI: -34.27, -7.77), VO2max (β: -1.90, 95% CI: -2.42, -1.38), VO2AT (β: -1.16, 95% CI: -1.53, -0.80), RERpeak (β: -0.03, 95% CI: -0.05, -0.02), and QoL (β for ln [KCCQ score]: -0.05, 95% CI: -0.10, -0.0006) levels. However, the obesity and normal BMI groups were not significantly different in terms of HRpeak (β: 1.07, 95% CI: -1.71, 3.85). Conclusions Our study found that in patients with chronic heart failure, increasing body mass index is associated with poor exercise capacity and functional status. Our findings underscore the potential importance of optimizing weight management among individuals with chronic heart failure to improve functional status.